Prompt KS0 production in pp collisions at √s=0.9 TeV - Aaij, Roel; Bachmann, Sebastian; Deissenroth, Marc; Eisele, Franz; Färber, Christian; Hansmann-Menzemer, Stephanie; Krocker, Georg Alexander; Linn, Christian; Marks, Jörg; Stahl, Sascha; Uwer, Ulrich; Wandernoth, Sebastian; et al. (Physics letters, 2010)
The production of KS0 mesons in pp collisions at a centre-of-mass energy of 0.9 TeV is studied with the LHCb detector at the Large Hadron Collider. The luminosity of the analysed sample is determined using a novel technique, involving measurements of the beam currents, sizes and positions, and is found to be 6.8±1.0 μb−1. The differential prompt KS0 production cross-section is measured as a function of the KS0 transverse momentum and rapidity in the region 0<pT<1.6 GeV/c and 2.5<y<4.0. The data are found to be in reasonable agreement with previous measurements and generator expectations.
*LHCb Collaboration: R. Aaij, S. Bachmann, M. Deissenroth, F. Eisele, C. Färber, S. Hansmann-Menzemer, G. Krocker, C. Linn, J. Marks, S. Stahl, U. Uwer, S. Wandernoth, D. Wiedner, A. Zhelezov [und 615 weitere Personen]
Gesehen am 10.11.2022
Im Titel ist der Buchstabe S tiefgestellt
Im Titel ist die Zahl 0 hochgestellt
Im Titel steht der Buchstabe s unter dem Wurzelsymbol